Naming the enemy: how to fortify society against foreign disinformation while avoiding excessive vigilance to reliable media - Charlotte Wagnsson; Albin Östervall; Anton Angwald (Humanities & Social Sciences Communications)
Abstract In response to disinformation projected by authoritarian regimes and antagonistic actors, states and institutions implement various countermeasures to fortify the information space. This includes warnings and educational efforts. Paradoxically, such information, meant to counter disinformation, can render people excessively vigilant and skeptical of reliable information. Can this be avoided? This study assesses the idea that framing unreliable information as a foreign threat can enhance the effectiveness of media literacy training while reducing the risk of excessive skepticism toward trustworthy sources. The authors tested two media literacy training videos in a preregistered randomized controlled experiment with a between-subjects design, using a nationally representative sample of the Swedish population (N = 1054). One video focused on source criticism without referencing external threats, while the other focused on the problem of disinformation from foreign actors, specifically Russia. Unlike findings from the U.S., the results show that both experimental groups improved their ability to identify unreliable information without becoming more distrustful of credible information from domestic media, public service outlets, and government agencies. The group exposed to the external threat narrative demonstrated the highest level of discernment and greatest trust in credible information. These findings offer reason for cautious optimism about the potential of media literacy training. The article ends by problematizing the findings and suggesting avenues for future research.